2019
DOI: 10.1371/journal.pone.0220562
|View full text |Cite
|
Sign up to set email alerts
|

A plant biostimulant made from the marine brown algae Ascophyllum nodosum and chitosan reduce Fusarium head blight and mycotoxin contamination in wheat

Abstract: Fusarium head blight (FHB) caused by Fusarium graminearum is a disease that results in yield loss and mycotoxin contamination in wheat globally. This study assessed the effect of a plant biostimulant prepared from a brown macroalga Ascophyllum nodosum (Liquid Seaweed Extract; LSE) alone and in combination with chitosan in controlling Fusarium. Wheat seedlings drenched with LSE and chitosan in combination showed reduced severity of F. graminearum infection on leaves as evidenced by a significant reduction in ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(27 citation statements)
references
References 53 publications
3
24
0
Order By: Relevance
“…Here we have used a sand culture system to grow A. thaliana with extracts from A. nodosum (“AN”), or D. potatorum (“DP”), or their combination (“AN/DP”). Studies on biostimulants and their impacts on plant disease establishment and progress have been reported (see for example, Gunupuru et al, 2019 ) although a comprehensive time course study of a root pathogen, and in this case an oomycete root pathogen, in the model plant A. thaliana has not been undertaken. The advantage of using A. thaliana , apart from its incredibly well detailed and characterized genome, is that there is a growing body of information around the interaction of this host with a range of oomycete pathogens including P. cinnamomi ( Robinson and Cahill, 2003 ; Rookes et al, 2008 ), Phytophthora porri ( Roetschi et al, 2001 ) and P. parasitica ( Le Berre et al, 2017 ), Hyaloperonospora arabidopsidis ( Kunz et al, 2008 ; Ried et al, 2019 ), and Albugo candida ( Cooper et al, 2008 ), but none on their interactions with biostimulants.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here we have used a sand culture system to grow A. thaliana with extracts from A. nodosum (“AN”), or D. potatorum (“DP”), or their combination (“AN/DP”). Studies on biostimulants and their impacts on plant disease establishment and progress have been reported (see for example, Gunupuru et al, 2019 ) although a comprehensive time course study of a root pathogen, and in this case an oomycete root pathogen, in the model plant A. thaliana has not been undertaken. The advantage of using A. thaliana , apart from its incredibly well detailed and characterized genome, is that there is a growing body of information around the interaction of this host with a range of oomycete pathogens including P. cinnamomi ( Robinson and Cahill, 2003 ; Rookes et al, 2008 ), Phytophthora porri ( Roetschi et al, 2001 ) and P. parasitica ( Le Berre et al, 2017 ), Hyaloperonospora arabidopsidis ( Kunz et al, 2008 ; Ried et al, 2019 ), and Albugo candida ( Cooper et al, 2008 ), but none on their interactions with biostimulants.…”
Section: Discussionmentioning
confidence: 99%
“…Probable serine/threonine-protein kinase PBL20, cytoplasmic receptor-like protein kinases, may be involved in plant defense signaling Zhang et al, 2010 In other host−pathogen systems treatment with seaweed extract-based biostimulants have indicated that disease incidence and severity may be reduced following infection. For example, commercial seaweed extracts from A. nodosum and D. potatorum were found to suppress disease caused by Plasmodiophora brassicae in broccoli (Wite et al, 2015) and an extract from A. nodosum reduced the severity of Fusarium head blight caused by F. graminearum in wheat (Gunupuru et al, 2019). It is worth noting the diversity in seaweed extracts.…”
Section: Pbl20mentioning
confidence: 99%
“…During the greenhouse experiments, by using as host plant the cultivar Falat (bread wheat) they observed a disease severity of 29% and 27% in chitosan and chitosan nanoparticles treated plants, while the plants treated with the tilt fungicides reached 0.33% of disease severity after three weeks of inoculation [ 55 , 56 ]. Another study [ 57 ] combined chitosan with a plant biostimulant, the liquid seaweed extract (LSE) from a brown macroalga and evaluated the efficacy of chitosan and LSE, alone or combined, against F. graminearum growth. In vitro, no synergistic effect of LSE and chitosan was observed on mycelial growth and chitosan at 0.001% showed 43% of growth inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the authors also evaluated the induction of transcription of TaPR1 , TaPR2, and TaPR3 in wheat seedlings at 24, 48, and 72 h post inoculation (hpi). TaPR1 and TaPR2 showed the greatest up-regulation at 48 hpi (25 and 500-fold, respectively) and were significantly induced in all the chitosan-based treatment compared to the plants subjected only to F. graminearum inoculation (10 and 200-fold, respectively) [ 57 ]. These results are in agreement with data obtained from our experiments since we observed a consistent F. graminearum growth inhibition by applying chitosan in vitro at different concentrations (0.01–1%) and a significant reduction of FHB incidence and severity during the greenhouse experiments by applying chitosan at 0.5%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation